Using electrical stimulation to control standing posture. - Abbas, J.J.
Describes strategies that have been used to control standing posture with electrical stimulation and reviews research efforts aimed at improving the performance of stimulation systems
Keywords: Electrical stimulation; Neuromuscular stimulation; Research efforts; Spinal cord injury; Standing posture; Stimulation systems